ITGBL1 promotes cell migration and invasion through stimulating the TGF‐β signalling pathway in hepatocellular carcinoma. (14th June 2020) - Huang, Wei; Yu, Demin; Wang, Mingjie; Han, Yue; Lin, Junyu; Wei, Dong; Cai, Jialin; Li, Bin; Chen, Peizhan; Zhang, Xinxin
Abstract: Objectives: Integrin beta‐like 1 (ITGBL1) is involved in the migration and invasion of several cancers; however, its roles in the development and progression of hepatocellular carcinoma (HCC) remain largely unknown. Materials and methods: Immunohistochemistry staining was used to investigate the expression pattern of ITGBL1 and its prognostic values in HCC patients. The transwell, wound‐healing assays, xenograft and orthotopic mouse models were employed to determine the effects of ITGBL1 on HCC cell migration and invasion in vitro and in vivo. The biological mechanisms involved in cell migration and invasion caused by ITGBL1 were determined with Western blotting and RT‐PCR methods. Results: ITGBL1 expression was significantly increased in HCC tissues compared to adjacent normal tissues. Patients with higher ITGBL1 expression were associated with more reduced overall survival. ITGBL1 overexpression promoted migration and invasion in SMMC‐7721 and HepG2 cells in vitro and in vivo, whereas knockdown or knockout ITGBL1 in CSQT‐2 cells significantly reduced cell migration and invasion abilities. In SMMC‐7721 cells, ITGBL1 overexpression stimulated TGF‐β/Smads signalling pathway, along with the KRT17 and genes involved in the epithelial‐mesenchymal transition (EMT). In contrast, ITGBL1 knockout inhibited the TGF‐β/Smads signalling pathway in CSQT‐2 cells. Conclusions: These findings suggested that ITGBL1 promoted migration and invasion in HCC cells by stimulating the TGF‐β/Smads signalling pathway. ITGBL1 could be a promising prognostic biomarker, as well as a potential therapeutic target in HCC.